Digitalisasi Komunikasi Komunitas Kolok Sebagai Upaya Pelestarian Budaya Lokal Dan Religiusitas Masyarakat Bengkala - Komang Ayu Saraswati; IG Agung Jaya Suryawan; I Nyoman Miarta Putra (Kamaya: Jurnal Ilmu Agama, 2026)
The development of digital technology has significantly transformed efforts to preserve local culture, including within linguistically distinctive communities such as the Kolok community in Bengkala Village, Buleleng Regency. This community uses Kata Kolok, a natural sign language that functions not only as a means of communication but also as a cultural identity as well as a medium for social and religious expression. This study aims to analyze the role of communication digitalization in preserving local culture, strengthening social inclusion, and sustaining the religiosity of the Kolok community amid digital transformation. This research employs a qualitative descriptive approach, with data collected through participatory observation, in-depth interviews, documentation, and literature review. The informants include members of the Kolok community, customary leaders, religious leaders, village officials, and Bengkala residents. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing, supported by source and method triangulation. The findings show that digitalization through the LETSIGN application, audiovisual documentation, and social media plays an important role in preserving Kata Kolok and expanding cross-group learning access. Digital tools also enhance social inclusion by improving communication between Kolok and non-Kolok residents, thereby reducing interaction barriers in social and customary activities. In addition, digital technology supports the documentation of cultural and religious practices, including traditional ceremonies and performing arts, which strengthens the community’s collective identity. However, challenges remain in understanding cultural context, which cannot be fully represented through digital media alone. In conclusion, communication digitalization serves not only as a documentation tool but also as a strategic instrument for cultural preservation, social inclusion enhancement, and the sustainable maintenance of the Kolok community’s religiosity in an adaptive response to ongoing technological development.